Arachidonic acid regulation of steroid synthesis: New partners in the signaling pathway of steroidogenic hormones - Castilla, R. (2004)
Although the role of arachidonic acid (AA) in trophic hormone-stimulated steroid production in various steroidogenic cells is well documented, the mechanism responsible for AA release remains unknown. We have previously shown evidence of an alternative pathway of AA generation in steroidogenic tissues. Our results are consistent with the hypothesis that, in steroidogenic cells, AA is released by the action of a mitochondrial acyl-CoA thioesterase (MTE-I). We have shown that recombinant MTE-I hydrolyses arachidonoyl-CoA to release free AA. An acyl-CoA synthetase specific for AA, acyl-CoA synthetase 4, has also been described in steroidogenic tissues. In the present study we investigate the new concept in the regulation of intracellular levels of AA, in which trophic hormones can release AA by mechanisms different from the classical PLA 2-mediated pathway. Inhibition of ACS4 and MTE-I activity by triacsin C and NDGA, respectively results in a reduction of StAR mRNA and protein abundance. When both inhibitors are added together there is a synergistic effect in the inhibition of StAR mRNA, StAR protein levels and ACTH-stimulated steroid synthesis. The inhibition of steroidogenesis produced by the NDGA and triacsin C can be overcome by the addition of exogenous AA. In summary, results shown here demonstrate a critical role of the acyl-CoA synthetase and the acyl-CoA thioesterase in the regulation of AA release, StAR induction, and steroidogenesis. This further suggests a new concept in the regulation of intracellular distribution of AA through a mechanism different from the classical PLA2-mediated pathway that involves a hormone-induced acyl-CoA synthetase and a hormone-regulated acyl-CoA thioesterase.